Synthesis of CdIn2Se4and Cu0.5Ag1.5InSe3compounds via chemical and solid-State methods - Viratchara Laokawee (2018)
CdIn 2 Se 4 and Cu 0.5 Ag 1.5 InSe 3 are high-performance thermoelectric materials. In this study, both CdIn 2 Se 4 and Cu 0.5 Ag 1.5 InSe 3 powders were synthesized using a microwave and solution method followed by annealing in nitrogen atmosphere. CdIn 2 Se 4 was synthesized by two routes. First, CdSe was prepared using a microwave method. Second, In metal was prepared using a solution method. The prepared metals were annealed in nitrogen atmosphere. From the x-ray diffraction (XRD) results, CdIn 2 Se 4 was observed as the main phase with CdSe and In 2 O 3 as contaminant phases. The synthesis of Cu 0.5 Ag 1.5 InSe 3 was also divided into two steps. First, CuAg and Se were prepared using a microwave method. Second, In metal was prepared using a solution method. The prepared metals were annealed in nitrogen atmosphere. From the XRD results, Cu 0.5 Ag 1.5 InSe 3 was observed as the main phase with Cu 0.5-x Ag 1.5-y In x+y Se and Se as contaminant phases. © 2014 TMS.